Analisis UU Sistem Pendidikan Nasional Nomor 20 Tahun 2003 dan Implikasinya terhadap Pelaksanaan Pendidikan di Indonesia - Rahman, Abdul; Naldi, Wahyu; Arifin, Adiyatna; Mujahid R, Fazlur (JOEAI (Journal of Education and Instruction), 2021)
The purpose of this research is to analyze Law No. 20 of 2003 on the National Education System, and its implications in the implementation and implementation of education in Indonesia today. This study uses a qualitative approach. Problem solving using content analysis, which is from many sources. The results of the study, in implementing the existence of Law No. 20 of 2003 on the National Education System, raises pros and cons, there are at least three opinions addressing the existence of Law No. 20 of 2003 on the National Education System, namely: first, immediately improve and replace irrelevant articles. Second, adding new articles that have not been accommodated in the Law, so that this Law can be aligned with the dynamics, can be by holding revisions periodically. Third, evaluate, control and improve derivative regulations from the implementation of Law No. 20 of 2003 on the National Education System periodically in order to accommodate the development and dynamics of the times. Conclusion, It is common if in the implementation of several articles in Law No. 20 of 2003 on the National Education System is found things that cause polemics, pros and cons, and multi-interpretation in the community, so there needs to be further revisions in order for this Law to be in line with existing dynamics. Keywords: Analysis of Law, Law No. 20 of 2003, National Education System